ChemInform Abstract: Rhodium‐Catalyzed Annulation of Arenes with Alkynes Through Weak Chelation‐Assisted C—H Activation. Issue 14 (March 2016) - Yang, Yudong; Li, Kaizhi; Cheng, Yangyang; Wan, Danyang; Li, Mingliang; You, Jingsong
Abstract: Review: [34 refs.